Smart Cities: Issues and Challenges towards a human centric paradigm - Δημητρακόπουλος, Νεκτάριος (Πανεπιστήμιο Πελοποννήσου, 2022)
The technological developments of recent years have greatly helped to raise the human standard of living and optimize the living conditions of a large portion of the human population. Technology is now present in almost every aspect of everyday life, from communicating with other people and getting around, to using personal information and receiving medical care. All of the above has been made possible through applications that have been created with the help of "smart" devices and the internet and which overwhelm humanity every day. Efforts are constantly being made to transfer and utilize this technological development to a greater level, at the level of the city, within which various daily activities should be coordinated with the aim of improving the lives of citizens. With such a city it is now known as a "Smart" City. By extension, the term "smart" city refers to the simplification of procedures available to the general public in order to improve their living conditions. This paper examines and presents the "smart city" phenomenon. The purpose of this paper is to present and analyze the phenomenon of the "smart" city and ethical challenges through thorough bibliographic research at a global level, contributing to the dissemination of updated information, due to the speed of developments in the field of IT and society.
Έξυπνες πόλεις: Θέματα και προκλήσεις προς ένα ανθρωποκεντρικό παράδειγμα
Μ.Δ.Ε. 111
Keywords: Smart city, Internet of things (IoT), New technologies,Innovation, Sustainable development, Ethical Issues